ORGANIZATIONAL SILENCE: SUATU PENGHAMBAT DALAM MEWUJUDKAN KREATIFITAS ORGANISASIONAL - Berta Bekti Retnawati (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2003)
There are powerful forces in many organzations that cause widespread withholding of information about potential problems or issues by employess, this collective-level phenomenon as ‘organizational silence’. One significant effect of organizational silence relates to lack of organizational creativity.There are five major organizational factors that enhance creativity in a work environment: organizational climate, leadership style, organizational culture, resources and skills, the structure and system of an organization.Keywords: organizational silence, organizational creativity